The Effect of Integrity and Work Culture on Employee Performance in the Regional Financial Management Agency of Bekasi Regency - Sri Wahyuningsih; Mubarok Mubarok (Eduvest - Journal of Universal Studies, 2021)
The main problem in this research is how big the influence of integrity and work culture on employee performance at the Bekasi District Financial Management Agency, either simultaneously or partially. The author's purpose of conducting this research is to determine and analyze the Integrity and Work Culture on Employee Performance and the magnitude of the Influence of Integrity and Work Culture on Employee Performance in the Regional Financial Management Agency of Bekasi Regency, either simultaneously or partially. The method used in this study is a method with a descriptive and verification approach. The population in this study were employees of the Regional Financial Management Agency of Bekasi Regency, amounting to 50 people, of which all of the population were sampled. The data in this study is primary data, where the data is obtained from respondents' answers to the questionnaires that the authors distribute. The results of the data analysis that the author has done, the results show that there is a simultaneous and partial influence of integrity and work culture on employee performance at the Bekasi Regency Financial Management Agency, but when viewed partially, work culture affectts employee performance more than integrity.